Osteogenic and Angiogenic Profiles of Mandibular Bone-Forming Cells - Veselá, Barbora; Švandová, Eva; Bobek, Jan; Lesot, Hervé; Matalová, Eva (Frontiers in Physiology, 2019)
The mandible is a tooth-bearing structure involving one of the most prominent bones of the facial region. Mesenchymal cell condensation is the first morphological sign of osteogenesis, and several studies have focused on this stage also in the mandible. Little information is available about the early post-condensation period, during which avascular soft condensation turns into vascularized bone, and all three major bone cell types; osteoblasts, osteocytes and osteoclasts; differentiate. In the mouse first lower molar region, the post-condensation period corresponds to the prenatal days 13 to 15. If during this critical period, when osteogenesis reaches the point of major bone cell differentiation and their first complex set, vascularization already has to play a critical role, one should be able to show molecular changes which support both types of cellular events. The aim of the present report was to follow in organ context the expression of major osteogenic and angiogenic markers and identify those that are up- or downregulated during this period. To this end, PCR array was applied covering molecules involved in osteoblastic cell proliferation, commitment or differentiation, extracellular matrix (ECM) deposition, mineralisation, osteocyte maturation, angiogenesis, osteoclastic differentiation and initial bone remodelling. From 161 analysed osteogenic and angiogenic factors we found that the expression of 37 was altered when comparing the condensation stage with the bone stage. The results presented here provide a molecular survey of the early post-condensation stage of mandibular/alveolar bone development which has not yet been investigated in vivo.